Analisis Pengaruh Angka Melek Huruf Dan Angka Harapan Hidup Terhadap Kemiskinan di Provinsi Sumatera Utara - Harbain, Harbain; Harahap, Muhammad Harfandi (Economic Development Progress, 2024)
The Poverty is inability residents to meet their basic living needs Although the literacy rate  of the and life expectancy is highly but poverty still high too, especially in North Sumatera Province at 2012-2023 periods. The method of research is secondary data collecting from  North Sumetera central bureau  of statictic, Internet site, Books, Journal and others which relevant to the research. Location of the rearsch is 33 district/  city around North Sumatera. The result of multiple  linier regression  which  SPSS 25 processing was Y = 132.516  -0.891  X1– 0.502 X2 which means constant value is 132.5162, the influence of the the literacy rate   is negative  and significant a total of 0.891 and the influence of the life expectancy is negative  and significant a total of – -0.502. That is phenomenon of this research. The goal of research is how the influence of the the literacy rate  of the and life expectancy against poverty in North Sumatera Province.